Metabolic responses of wheat seedlings to osmotic stress induced by various osmolytes under iso-osmotic conditions. - Eva Darko; Balázs Végh; Radwan Khalil; Tihana Marček; Gabriella Szalai; Magda Pál; Tibor Janda (PLoS ONE)
Many environmental stresses cause osmotic stress which induces several metabolic changes in plants. These changes often vary depending on the genotype, type and intensity of stress or the environmental conditions. In the current experiments, metabolic responses of wheat to osmotic stress induced by different kinds of osmolytes were studied under iso-osmotic stress conditions. A single wheat genotypes was treated with PEG-6000, mannitol, sorbitol or NaCl at such concentrations which reduce the osmotic potential of the culture media to the same level (-0.8MPa). The metabolic changes, including the accumulation of proline, glycine betaine (GB) and sugar metabolites (glucose, fructose, galactose, maltose and sucrose) were studied both in the leaves and roots together with monitoring the plant growth, changes in the photosynthetic activity and chlorophyll content of the leaves. In addition, the polyamine metabolism was also investigated. Although all osmolytes inhibited growth similarly, they induced different physiological and metabolic responses: the CO2 assimilation capacity, RWC content and the osmotic potential (ψπ) of the leaves decreased intensively, especially after mannitol and sorbitol treatments, followed by NaCl treatment, while PEG caused only a slight modification in these parameters. In the roots, the most pronounced decrease of ψπ was found after salt-treatments, followed by PEG treatment. Osmotic stress induced the accumulation of proline, glycine betaine and soluble sugars, such as fructose, glucose, sucrose and galactose in both the root and leaf sap. Specific metabolic response of roots and leaves under PEG included accumulation of glucose, fructose and GB (in the roots); sucrose, galactose and proline synthesis were dominant under NaCl stress while exposure to mannitol and sorbitol triggered polyamine metabolism and overproduction of maltose. The amount of those metabolites was time-dependent in the manner that longer exposure to iso-osmotic stress conditions stimulated the sugar metabolic routes. Our results showed that the various osmolytes activated different metabolic processes even under iso-osmotic stress conditions and these changes also differed in the leaves and roots.